„Wielopostaciowość śmierci” w poezji Anny Świrszczyńskiej. Na marginesie rozważań Mariana Maciejewskiego - Pawlik, Aleksandra (Colloquia Litteraria, 2014)
‘Multiformity of death’ in Anna Świrszczyńska’s poetry On the margins of Marian Maciejewski’s reflections The article attempts to interpret the Budowałam Barykadę [I Constructed a Barricade] volume by Anna Świrszczyńska in the light of Marian Maciejewski’s reflections on the ‘multiformity of death’ in Antoni Malczewski’s narrative poem Maria. Świrszczyńska’s collection of poems concentrates mainly on corporeality in the face of war experience; it reveals the tragic situation of human existence entangled in mechanisms of history. The author, using the methodology suggested by Maciejewski, combines the concept of ontic death with the existential current in research that concerns corporeality. Such a synthesis allows for creation of a method of interpretation that enriches the already existing interpretative contexts of Świrszczyńska’s writings and discovers new ones.